Real-world incidence of inflammatory bowel disease among patients with other chronic inflammatory diseases treated with interleukin-17a or phosphodiesterase 4 inhibitors. (3rd October 2019) - Emond, Bruno; Ellis, Lorie A.; Chakravarty, Soumya D.; Ladouceur, Martin; Lefebvre, Patrick
Abstract: Objectives: (1) To assess the real-world incidence of inflammatory bowel disease (IBD) in patients with or without other chronic inflammatory diseases (CIDs), and (2) to understand whether IBD incidence differs in CID patients receiving interleukin-17a signaling antagonists (anti-IL-17a) or phosphodiesterase 4 inhibitors (PDE4i) versus patients using a biologic not indicated for IBD or biologic-naïve patients. Methods: The MarketScan Research Databases (January 2010–July 2017) were used. A CID population was created from patients with ankylosing spondylitis, psoriatic arthritis, psoriasis or rheumatoid arthritis (RA). The CID population was stratified into different cohorts based on the baseline treatments received: (1) anti-IL-17a, (2) PDE4i, (3) biologic-naïve, and (4) non-IBD-indicated biologic (i.e. biologics not indicated for the treatment of IBD and excluding anti-IL-17a and PDE4i); a non-CID cohort was also created. The 1 year incidence rate (IR) of IBD was compared between cohorts using a logistic regression model adjusting for baseline characteristics. Results: CID cohorts included older patients than the non-CID cohort (mean age range: 48.4–54.4 versus 46.3 years). The 1 year IR of IBD was 1.41% in the anti-IL-17a cohort ( N = 355), 0.68% in the PDE4i cohort ( N = 2195), 0.47% in the biologic-naïve cohort ( N = 424, 767), 0.51% in the non-IBD-indicated biologic cohort ( N = 56, 317) cohort and 0.25% in the non-CID cohort ( N = 1, 008, 436). After 1 year of follow-up, the odds of having IBD were 2.85 ( p = .0213) and 1.42 ( p = .1891) times higher in the anti-IL-17a and PDE4i cohorts, respectively, compared to the biologic-naïve cohort, and 2.86 ( p = .0253) and 1.21 ( p = .4978) times higher compared to the non-IBD-indicated biologic cohort. Similar results were observed in sensitivity analyses where patients with RA only were excluded (since anti-IL-17a and PDE4i agents are not indicated for RA). Conclusions: Anti-IL-17a treatment was associated with a nearly three-fold higher risk of IBD in CID patients. Treatment decisions for patients with CIDs should take into account the risk of developing of IBD.